KOMPOS PELLET DARI AMPAS KOPI GAYO ESPRESSO DENGAN STARTER ALAMI - Zahra Fona; Eka Maryan Putri; Ummi Habibah; Raudah Raudah; Zuhra Amalia (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2021)
Compost is very useful for soil improvement, maintaining soil stability and fertility, and increasing micro nutrients required by plants. This study aims to determine the effect of using natural starters: chicken manure (A), cow dung (S), and EM4 on composting time, compost pH, and the macro nutrient content made from Gayo espresso coffee waste. The waste of Gayo espresso coffee, which is available abundantly available in coffee shops, which is used as raw material for composting. Starters the form of A, S, a mixture of A with S, and EM4 are used to shorten composting time, and improve compost characteristics to conform to SNI standards. Gayo espresso coffee waste is mixed with starter A, starter mixture S. starter mix, and EM4 then fermented in a closed container. Compost pH measurements during the composting process are carried out every day until the pH is close to neutral, which indicates the compost is ripe. After composting, the products that were quickly formed from all treatment variables were tested for macro nutrient levels in the form of N, P, K and C / N ratios. The compost is printed in the form of pellets using a pelletizer mold. The test results showed that the use of 200g starter A (cow dung) and 6 ml EM4 produced compost within 25 days. The average acidity of the compost for all treatments ranged from 6.83. Micro nutrient content in the compost is 1.11% nitrogen, 0.81% phosphorus, 1.64% potassium and C / N ratio 11.06, according to SNI standards.